Copper homeostasis and cuproptosis in myocardial infarction: molecular mechanisms, treatment strategies and potential therapeutic targets - Shen, Zhen; Liu, Zhichao; Cai, Siqi; Fu, Huanjie; Gan, Yongkang; Li, Xiaofeng; Wang, Xizhen; Liu, Chang; Ma, Wenjia; Chen, Jinhong; Li, Ningcen (Frontiers in Pharmacology, 2025)
Copper (Cu), an essential trace element for normal bodily functions, plays a pivotal role in cardiac muscle biology and is critical for cardiac function and metabolism. Recent research increasingly links Cu-related cell death (cuproptosis) to diseases like myocardial infarction (MI). Cu overload drives cuproptosis via mitochondrial dysfunction, lipoylated protein aggregation, and Fe-S cluster reduction, inducing proteotoxic stress and linking inflammatory/ROS pathways to MI progression. Therefore, it can be hypothesized that cuproptosis is a novel therapeutic target for MI. In this review, we explore the primary molecular mechanisms, treatment strategies and potential therapeutic targets involved in cuproptosis. Moreover, the insights obtained from this review provide a novel perspective on the pathogenesis of MI and new targets for its intervention.